An Interdisciplinary Team-Based Learning Experience in Clinical Ethics - Andrea Gregg; William Allen; Erik Black; Richard Davidson; Wayne McCormack (MedEdPORTAL, 2013)
Abstract This team-based learning resource provides the framework for health professions students from multiple health colleges to actively engage in interprofessional dialogue about ethical codes and bioethical principles from across the health professions, apply these codes/principles to historical and present-day ethical dilemmas, and experience interprofessional teamwork in resolving ethical dilemmas. A set of eight multiple-choice questions was used to assess the effectiveness of student preparation for this activity. Data related to the questions was derived from a large (N = 626) sample of interprofessional learners from 10 different health science disciplines at a large academic health science center in the Southeastern US. Average performance across professions ranged from 16.5 to 20.27 on a 32-point scale (featuring eight questions, each worth four points). The mean team performance on the team readiness assurance test (M = 26.47, SD = 2.70) significantly exceeded (p < .01) individual mean performance on the individual readiness assurance test (M = 17.98, SD = 5.63). There was no statistically significant difference in team readiness assurance test score between teams (p = .37).